2010
DOI: 10.1016/j.jfoodeng.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and robust multi-objective optimization of food processing: A novel approach with application to thermal sterilization

Abstract: a b s t r a c tThe optimization of thermal processing of foods is a topic which has received great attention during the last decades. The majority of the authors have considered the use of single-objective (criteria) for the optimization. However, the simultaneous optimization of several objectives is much more realistic and desirable, but the associated non-linear programming problems can be very challenging to solve. Here, we describe an efficient and robust multi-criteria optimization method which can be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…New method requires process optimisation so as to find the optimal balance between heating temperature and the process time in order to maximise the final nutrient retention and assure sufficient microbiological lethality. Furthermore, maximisation of energy efficiency and minimisation of total process time should also be taken into account (Send ın et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…New method requires process optimisation so as to find the optimal balance between heating temperature and the process time in order to maximise the final nutrient retention and assure sufficient microbiological lethality. Furthermore, maximisation of energy efficiency and minimisation of total process time should also be taken into account (Send ın et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Out of them, NBI method [6] has a clear geometric idea and simple to use. Due to that, in the last decade, NBI method has been used extensively [1,14,19,21,22,24,31,34,37,43]. However, NBI has several drawbacks.…”
Section: Mlpmentioning
confidence: 99%
“…However, most optimization studies reported in food engineering refer to singleobjective optimization. Only a few researchers proposed multi-response strategies in the analysis of different food processes: bulk-grain handling [11]; thermal processing [12][13][14][15][16][17]; conventional drying [18][19][20]; osmotic dehydration [10,[21][22][23][24][25][26][27][28]; baking [29][30][31][32][33]; roasting [34,35]. Pasteurization process requires optimization with the purpose of simultaneously diminish costs and undesired effects on the quality in the resulting product.…”
Section: Introductionmentioning
confidence: 99%